Witogai Kamuu, Menemukan Wajah Allah yang “Memanggil Pulang”. Sebuah TelaahTeologis Praktek Rekonsiliasi Suku Mee, Papua - Lela, Emanuel Richardus Buang (Perspektif, 2019)
The article tries to respond theologically the praxis of the so-called witogai kamuu, a reconciliation rite among the ethnic Mee in Papua. It is an exploration and evaluation on the meaning of witogai kamuu, which has traditionally been carried out among the Mee. The main intention is to improve the praxis of reconciliation for the better future of the people and their society. Suggestions and recommendations will be offered at the end of the article directed primarily to the local Church, the active subject of witogai kamuu. The writer is convinced that the local Church is the one who is expected the most to work more seriously in promoting peace within the Mee society. He also believes that the sacrament of reconciliation in particular is the very important means among the Catholics that could be made known among the Mee in particular and within the society in general.